A Retrospective View of an ESP Teacher Education Programme - Celani, Maria Antonieta Alba (The ESPecialist, 2012)
The aim of this paper is to look back at a teacher education programme carried out in the 80’s as part of the Brazilian National ESP Project1 and reflect on its nature in the light of current ideas on teacher education. After a very brief description of the context of the programme, the paper concentrates on the features of the teacher education component, emphasising its developmental, reflective nature and trying to examine it in the context of reflective learning as understood today.